Latest evidence of microwave ablation for papillary thyroid microcarcinoma compared with surgery: A systematic review and meta-analysis - Feng, Jie; Jiang, Yizhou; Feng, Yiyan (Frontiers in Oncology, 2023)
Abstract Background The most typical thyroid gland malignant lesion is papillary thyroid cancer (PTC). In many nations, the prevalence of thyroid cancer (TC) is rising, particularly papillary thyroid microcarcinoma (PTMC). Microwave ablation (MWA) has been gradually carried out in some patients with benign thyroid nodules, some low-risk PTMC, and metastatic lymph nodes in the neck. The role and safety of MWA remain controversial topics. So we conducted this study to provide the latest evidence of MWA for PTMC compared with surgery. Methods Patients' postoperative outcomes (duration of hospital stay and hospitalisation expenditures), intraoperative outcomes (surgery time, blood loss, and incision size), and follow-up outcomes were all examined (complication rate, recurrence rate, and lymph node metastasis). The effectiveness and safety of MWA versus surgery for PTMC patients were compared using the weighted mean difference (WMD) and odds ratio (OR). Results In total, we included 7 articles (7 trial comparisons) which contained 1, 567 PTMC patients. The results showed that MWA had significant advantages in operative time (WMD = -53.47, 95% CI: -67.62 to -39.32), postoperative hospital stay (WMD =-4.59, 95% CI: -6.40 to -2.77), hospitalization costs (WMD= -70.06, 95% CI: -90.93 to -49.19), blood loss (WMD =-28.07, 95% CI: -33.77 to -22.38), incisions size (WMD =-59.69, 95% CI: -67.79 to -51.59), and complication rates (OR = 0.28; 95% CI: 0.18 to 0.42) compared with surgery. It also showed that recurrence rates and risk of lymph node metastasis are similar to surgery. Conclusions: For PTMC patients, MWA could be an efficient, safe, and affordable therapy.